Fenomena Sosial Mahasiswa Jurusan Seni di Universitas Seni Tokyo Pada Anime Blue Period: Social Phenomenon of Art Students at Tokyo University of the Arts in Anime Blue Period - gilbran, issyaadhi; Arfianty, Rani (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
This study explains the basics of sociology by detailing the views of figures such as Comte, Durkheim, and Weber. The anime "Blue Period" reflects the reality of art students, especially in the struggle to enter Tokyo University of the Arts. This study uses a qualitative descriptive method approach. The results of the data analysis show that "Blue Period" is accurate in depicting the fierce competition to enter a prestigious art university. This anime reflects the reality of art students, including the sadness, struggles, and complex emotions they face in achieving their dreams. The title Blue Period itself is inspired by the work of Pablo Picasso, which reflects the melancholy feelings that are relevant to the struggles of art students. This study provides an in-depth understanding of sociology and details its relevance to the reality of art students' lives through the lens of the anime.